Hubungan Dukungan Suami dengan Keikutsertaan Akseptor KB IUD - Siti Yuriah; Linda Puspita Sari (Universitas Respati Indonesia, 2025)
Husbandly support is central to social relationships between individuals, as well as to the interactions that occur within a wife. It is traditional that everything must be done with the husband's approval. The family plays a crucial role in the choice of contraceptive method, as the mother reconsiders her choice. Husbandly support for the wife's contraceptive choice allows for continued use of an IUD, a strategy that helps reduce fertility. Often, the husband's lack of involvement results in a lack of information about reproductive health, particularly contraceptives. This study aims to determine the relationship between husband's support and IUD use. This research employed a quantitative research method with an accidental sampling approach, resulting in a sample size of 66 respondents, and data analysis using the chi-square test. The study was conducted at the Ririn Sevda Korini SKM.S.Keb Bd. The sample size was 40 respondents, with the criteria of mothers who would actively use contraception. The instruments used in this study were a questionnaire for document recording (interviews) and observation. The results of this study found a relationship between husband's support and the participation of IUD acceptors at the Ririn Sevda Korini, SKM, S.Keb Bd. This was demonstrated by statistical test results with a p-value of 0.000. Husband's support for prospective IUD acceptors includes information, practical assistance, emotional support, and assessments, such as encouragement or motivation, to encourage mothers to participate in long-term contraception (IUD).